2021
DOI: 10.1186/s12974-021-02170-7
|View full text |Cite
|
Sign up to set email alerts
|

Phthalide derivative CD21 attenuates tissue plasminogen activator-induced hemorrhagic transformation in ischemic stroke by enhancing macrophage scavenger receptor 1-mediated DAMP (peroxiredoxin 1) clearance

Abstract: Background Hemorrhagic transformation (HT) is a critical issue in thrombolytic therapy in acute ischemic stroke. Damage-associated molecular pattern (DAMP)-stimulated sterile neuroinflammation plays a crucial role in the development of thrombolysis-associated HT. Our previous study showed that the phthalide derivative CD21 attenuated neuroinflammation and brain injury in rodent models of ischemic stroke. The present study explored the effects and underlying mechanism of action of CD21 on tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…The neurological function of mice was assessed using modified neurological severity score (mNSS, ranging from 0 to 18), , Longa’s neurological deficit score (ranging from 0 to 5), , and Bederson score (ranging from 0 to 4) . These assessments were conducted both before and after CI/R modeling to monitor changes in the mice’s neuro-motor function.…”
Section: Methodsmentioning
confidence: 99%
“…The neurological function of mice was assessed using modified neurological severity score (mNSS, ranging from 0 to 18), , Longa’s neurological deficit score (ranging from 0 to 5), , and Bederson score (ranging from 0 to 4) . These assessments were conducted both before and after CI/R modeling to monitor changes in the mice’s neuro-motor function.…”
Section: Methodsmentioning
confidence: 99%
“…These cascade reactions also include cell death-associated damage-associated molecular patterns (DAMP) and subsequent inflammatory responses ( 45 ). DAMPs promote the local activation of microglia and induce the recruitment of leukocytes ( 46 ). In this microenvironment, immune cells secrete pro-inflammatory cytokines, such as IL-1β, IL-6, and TNF-α, which induce local or systemic inflammatory responses ( 46 , 47 ).…”
Section: Regulatory Role Of 17β-estradiol In Neuroinflammationmentioning
confidence: 99%
“…DAMPs promote the local activation of microglia and induce the recruitment of leukocytes ( 46 ). In this microenvironment, immune cells secrete pro-inflammatory cytokines, such as IL-1β, IL-6, and TNF-α, which induce local or systemic inflammatory responses ( 46 , 47 ). Accumulative evidence has revealed that such immune responses can aggravate cerebral ischemic injuries as well as promote nerve regeneration, attenuate inflammation, and improve tissue repair after stroke ( 48 , 49 ).…”
Section: Regulatory Role Of 17β-estradiol In Neuroinflammationmentioning
confidence: 99%
“…In the liver, MSR1 can activate neutrophil complement responses and worsen hepatitis. However, in the brain, it is more frequently observed in responses to DAMP signaling and can be beneficial during tissue damage [11,[43][44][45]. Indeed, MSR-1-mediated complement activation on neutrophils may have a different connotation within the brain, with synaptic pruning being dependent on the complement pathway.…”
Section: Neuronal Regeneration Attempts During Chronic Infection Are ...mentioning
confidence: 99%